2022
DOI: 10.3389/fpsyg.2022.1030634
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting students’ foreign language learning demotivation: From concepts to themes

Abstract: Demotivation is a common psychological phenomenon in foreign language learning. Having a good understanding of learners’ foreign language learning demotivation is conducive to enriching the fruits of psychological research on foreign language learning theoretically and practically by exploring effective ways to improve learners’ foreign language learning motivation. Therefore, this study entails an analysis of the selected literature from 2001 to 2021 to interpret the concept of foreign language learning demot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Therefore, Factor 1 is named demotivation. Both external and internal factors possibly result in English learning demotivation ( Gao et al, 2022 ; Gao and Liu, 2022 ). Demotivated learners experience low confidence caused by external factors, such as a change in learning environment (item 6) and possible highly challenging tasks in English class (item 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Factor 1 is named demotivation. Both external and internal factors possibly result in English learning demotivation ( Gao et al, 2022 ; Gao and Liu, 2022 ). Demotivated learners experience low confidence caused by external factors, such as a change in learning environment (item 6) and possible highly challenging tasks in English class (item 10).…”
Section: Resultsmentioning
confidence: 99%
“…The current study found students’ demotivation level to be higher than their exhaustion level, indicating that they might be more likely to experience reduced motivation in English learning, such as having declining English learning interest and self-confidence, than to feel physically and mentally exhausted in the process of learning English. Demotivation occurs in everyday English learning at different educational levels (e.g., high school and university levels; see Hassaskhah et al, 2015 ; Xaypanya et al, 2017 ; Gao et al, 2022 ; Gao and Liu, 2022 ). It could be caused by external factors, such as the incompetence of language teachers and inappropriate teaching materials or methods ( Kikuchi, 2009 ; Karaca and Inan, 2020 ; Wang and Guan, 2020 ; Wu et al, 2020 ), and internal factors, such as prior language learning experience, interest, anxiety and negative attitudes ( Kim, 2011 ; Shin-Hye, 2015 ; Xaypanya et al, 2017 ; Wang and Guan, 2020 ; Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning demotivation in the EFL context, researchers acknowledge this issue as a significant concern (Gao & Liu, 2022;Wu & Ding, 2022). Various factors contribute to this prevalent problem such as negative teacher behavior, loss of task value, low expectancy for success, problems with the learning environment, and lack of self-discipline (Zhou, Zhan, & Jawing, 2023).…”
Section: Demotivation For Attendancementioning
confidence: 99%
“…1.1 Demotivating Factors for Foreign Language Learning According to You and Liang (2022), demotivation is the reduction of motivation level caused by negative external factors. In foreign language learning, demotivation is a common aspect (Gao & Liu, 2022). From various research conducted, it is discovered that there are several aspects influencing students' demotivation, such as learning anxiety (Xaypanya et al, 2017), learning content (Meshkat & Ebrahimi, 2012) and also the nature of the target language (Husniyah, 2019), to cite a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From various research conducted, it is discovered that there are several aspects influencing students' demotivation, such as learning anxiety (Xaypanya et al, 2017), learning content (Meshkat & Ebrahimi, 2012) and also the nature of the target language (Husniyah, 2019), to cite a few. By knowing and understanding the demotivating factors, educators can find effective ways to improve learners' motivation (Gao & Liu, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%